EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK PROBLEM BASED LEARNING DALAM PENINGKATAN MANAJEMEN WAKTU BELAJAR PADA SISWA KELAS XI SMA NEGERI 9 PONTIANAK - Fitriatul Aulia, Sakina; Asrori, Muhammad; Yanti, Elli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of group guidance services using the Problem Based Learning (PBL) technique in improving learning time management among eleventh-grade students at SMA Negeri 9 Pontianak. The method used in this research is an experimental research method with a Pre-Experimental Design, specifically the One-Group Pretest–Posttest Design. The sample was selected using a non-probability sampling technique, namely purposive sampling, with a total of 8 students who had the lowest level of learning time management from a population of 117 students. Based on the data analysis results, the average pre-test score was 83.5, which falls into the low category, while the average post-test score increased to 121.1, which is categorized as high. Furthermore, the results of the statistical test using the Paired Sample T-test showed a t-value of 20.652 and a significance value (2-tailed) of 0.000. This indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (H₀) is rejected, meaning that there is a significant difference in students' learning time management before and after receiving group guidance services using the Problem Based Learning technique. Therefore, it can be concluded that group guidance services using the Problem Based Learning technique are effective in improving learning time management among eleventh-grade students at SMA Negeri 9 Pontianak.